2018
DOI: 10.1074/jbc.ra117.000860
|View full text |Cite
|
Sign up to set email alerts
|

Activation of renal ClC-K chloride channels depends on an intact N terminus of their accessory subunit barttin

Abstract: ClC-K channels belong to the CLC family of chloride channels and chloride/proton antiporters. They contribute to sodium chloride reabsorption in Henle's loop of the kidney and to potassium secretion into the endolymph by the stria vascularis of the inner ear. Their accessory subunit barttin stabilizes the ClC-K/barttin complex, promotes its insertion into the surface membrane, and turns the pore-forming subunits into a conductive state. Barttin mutations cause Bartter syndrome type IV, a salt-wasting nephropat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…According to our electrophysiological, biochemical, and imaging findings, the overexpression of the accessory subunit barttin succeeded in restoring at least in part the function of the expression-defective mutants G167V and A242E towards wild type levels. It is widely demonstrated that barttin is able to improve the stability of ClC-K channels by promoting complex glycosylation of the nascent proteins, thus facilitating effective exit from the ER and Golgi and sorting to the plasma membrane, besides modulating channel gating (Estévez et al, 2001;Waldegger et al, 2002;Hayama et al, 2003;Scholl et al, 2006;Janssen et al, 2009;Fischer et al, 2010;Wojciechowski et al, 2018a;Wojciechowski et al, 2018b). We could therefore likely infer that the same mechanism underlies BS mutant channels rescue.…”
Section: Perspectives For Bs Therapymentioning
confidence: 90%
See 1 more Smart Citation
“…According to our electrophysiological, biochemical, and imaging findings, the overexpression of the accessory subunit barttin succeeded in restoring at least in part the function of the expression-defective mutants G167V and A242E towards wild type levels. It is widely demonstrated that barttin is able to improve the stability of ClC-K channels by promoting complex glycosylation of the nascent proteins, thus facilitating effective exit from the ER and Golgi and sorting to the plasma membrane, besides modulating channel gating (Estévez et al, 2001;Waldegger et al, 2002;Hayama et al, 2003;Scholl et al, 2006;Janssen et al, 2009;Fischer et al, 2010;Wojciechowski et al, 2018a;Wojciechowski et al, 2018b). We could therefore likely infer that the same mechanism underlies BS mutant channels rescue.…”
Section: Perspectives For Bs Therapymentioning
confidence: 90%
“…Importantly, a molecule able to increase protein stability and prevent ER degradation, such as 17allylamino-17-demethoxygeldanamycin (17-AAG), an Hsp90 inhibitor, was reported to mitigate the BS symptoms in barttin R8L knock-in mice by likely enhancing the plasma membrane expression of ClC-K1/mutant barttin channels (Nomura et al, 2013). Barttin seems to interact with hydrophobic residues in helices B and J, at the outer surface of the ClC-K channels, through its short N-terminal and first TM1 helix (Tajima et al, 2007;Wojciechowski et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…; Wojciechowski et al . ). In the human, barttin regulates intracellular trafficking and the activity of both ClC‐Ka and ClC‐Kb.…”
Section: The Opportunity: Shared Characteristics Between Human and Zementioning
confidence: 97%
“…The activation of ClC‐Ka and ClC‐Kb is also enhanced by palmitoylation of barttin on its 55 and 56 cysteine residues (Wojciechowski et al . ). Point mutations on these two cysteine residues prevent post‐translational modification of barttin and deplete the currents produced by human ClC‐Ka and ClC‐Kb (Wojciechowski et al .…”
Section: The Opportunity: Shared Characteristics Between Human and Zementioning
confidence: 97%
See 1 more Smart Citation